2012
DOI: 10.1186/1742-2094-9-101
|View full text |Cite
|
Sign up to set email alerts
|

A single intraperitoneal injection of endotoxin in rats induces long-lasting modifications in behavior and brain protein levels of TNF-α and IL-18

Abstract: BackgroundSystemic inflammation might cause neuronal damage and sustain neurodegenerative diseases and behavior impairment, with the participation of pro-inflammatory cytokines, like tumor necrosis factor (TNF)-α and interleukin (IL)-18. However, the potential contribution of these cytokines to behavioral impairment in the long-term period has not been fully investigated.MethodsWistar rats were treated with a single intraperitoneal injection of LPS (5 mg/kg) or vehicle. After 7 days and 10 months, the animal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
99
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(104 citation statements)
references
References 61 publications
4
99
1
Order By: Relevance
“…Supporting the present findings, that a single challenge with LPS systemically can increase central TNF-a expression, Bossu et al (2012), showed that a single dose of LPS (5 mg/kg) was effective in increasing TNF-a expression in the hippocampus and PFC from 7 days after LPS challenge, lasting up to 10 months after challenge and that these changes were associated with cognitive impairments. These results indicate that TNF-a, through systemic LPS, can have lasting neuroinflammatory effects in the brain and may lead to cognitive decline.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Supporting the present findings, that a single challenge with LPS systemically can increase central TNF-a expression, Bossu et al (2012), showed that a single dose of LPS (5 mg/kg) was effective in increasing TNF-a expression in the hippocampus and PFC from 7 days after LPS challenge, lasting up to 10 months after challenge and that these changes were associated with cognitive impairments. These results indicate that TNF-a, through systemic LPS, can have lasting neuroinflammatory effects in the brain and may lead to cognitive decline.…”
Section: Discussionsupporting
confidence: 67%
“…It is known that peripherally stimulated monocytes affect the CNS via the BBB and the blood-CSF barrier and express cytokines, such as TNF-a (Ubogu et al, 2006). Indeed, this peripheral-central immune cross-talk is further supported by a study that showed how a single high dose of LPS (5 mg/kg) given IP was effective in increasing cytokine expression, particularly TNF-a, in the hippocampus and prefrontal cortex even 7 days after administration (Bossu et al, 2012). Thus, activation of peripheral inflammation can promote central activation and proliferation of microglia and subsequent production of cytokines within the brain itself (Bossu et al, 2012;Qin et al, 2007), providing a potential mechanism to explain the increase in microglia numbers noted within this study only in the hippocampus but not in the PFC.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Consistently, in a rodent model, IL-18 appears to be involved in the late stage of experimental neuroinflammation, possibly taking part in long-lasting modifications of brain functions, including progressive neurodegeneration and cognitive dysfunction [25]. Specifically regarding TBI, increased microglial activation can be present even several years after the trauma, triggering a long-lasting inflammatory response particularly in the subcortical regions of the brain [26].…”
Section: Discussionmentioning
confidence: 95%